Clinical Features and Surgical Treatment of Primary Pulmonary Lymphoma: A Retrospective Study - Shen, Hui; Zhou, Yaodong (Frontiers in Oncology, 2022)
Background Primary pulmonary lymphoma (PPL) is a rare clonal lymphoproliferative lung disease. The present study analyzes the clinical features, imaging data, pathologic characteristics, treatment, and prognosis of PPL patients, with the aim to discuss the appropriate diagnosis and therapy of PPL patients in thoracic surgery. Methods We performed a retrospective analysis on 36 patients with PPL confirmed by postoperative pathology between 2006 and 2020. We divided the patients into low-stage (IE) and high-stage (IIE) groups using modified Ann Arbor staging. The clinical manifestations, imaging findings, treatment modalities, and outcomes were evaluated. Results The female to male ratio was 1.57:1 and the median age was 55 (31–69) years old. The majority of the patients had stage IE disease (75%; 27 of 36) and 9 patients had stage IIE disease. Patients with advancing stage were more likely to have respiratory symptoms. The imaging findings presented solid nodule or mass, pneumonia-like consolidative pattern, ground-glass opacity, and mixed pattern. There were 31 cases of mucosa-associated lymphoid tissue lymphoma (MALT), 2 diffuse large B-cell lymphoma (DLBCL), 2 nodular sclerosing Hodgkin’s lymphoma, and 1 marginal zone B-cell lymphoma. Two patients were diagnosed with PPL and non-small cell lung cancer (NSCLC) synchronously (one AIS and MIS and one lung adenocarcinoma). All the patients received surgery. Nine patients received adjuvant therapy after surgery (five radiotherapy, two chemotherapy, and two chemoradiotherapy). Thirty-four patients had a median follow-up time of 31 months (follow-up range: 7–152 months). Of the 34 patients, 1 patient died of liver metastases and 1 patient died of intestinal metastases. Conclusions Our retrospective analysis suggested that most PPLs were indolent and had favorable prognosis, but the discrimination of PPL with other lung diseases was difficult. Preoperative biopsy and intraoperative frozen section examination might help in the surgical choice. Limited lung resection was enough for peripherally localized PPL.